2018
DOI: 10.29311/mas.v16i3.2792
|View full text |Cite
|
Sign up to set email alerts
|

‘My special, my special thing, and my camera!’ Using GoPro™ as a complementary research tool to investigate young children’s museum experiences.

Abstract: This paper discusses insights derived from a small-scale ethnographic study designed to explore young children's (aged three to six) everyday, lived experiences within a participatory family museum in southern England. Inspired by the childcentred work of Kirk (2014) this paper begins by examining the effectiveness of photo-elicitation interviews in accessing 'snap-shots' of children's perspectives of their museum visits. In the current study this method is complemented by the use of chest-mounted GoPro camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…It further enriches studies of navigating the library environment. Burbank et al (2018) found "the video captured by the chestmounted Go-Pro cameras is particularly illuminating when analyzed in the context of the postvisit interview data" with young children (p. 311). Given that characteristics of autism can include difficulty in conversational pragmatics and social communication, as well as challenges in turntaking while simultaneously writing, the use of RTAP allows subjects to clarify what they may not have been able communicate in real-time when completing their task (Paul et al, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…It further enriches studies of navigating the library environment. Burbank et al (2018) found "the video captured by the chestmounted Go-Pro cameras is particularly illuminating when analyzed in the context of the postvisit interview data" with young children (p. 311). Given that characteristics of autism can include difficulty in conversational pragmatics and social communication, as well as challenges in turntaking while simultaneously writing, the use of RTAP allows subjects to clarify what they may not have been able communicate in real-time when completing their task (Paul et al, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Like libraries, it has been opined that research conducted on children's experiences in museums has been focused on what children are, or should be learning, rather than what they themselves seek or value (Johanson & Glow, 2012). A noteworthy exception is an ethnographic study with children aged three to six using chest-mounted GoPro™ cameras to capture their experience in a participatory children's museum (Burbank et al, 2018). As part of a larger study designed to compare the utility of GoPro™ technology versus photo and drawing elicitation, it concluded that the unobtrusive GoPro™ camera yielded more powerful results than the other methods (Burbank et al, 2018).…”
Section: Application To School Library Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…For the last decades, the advances in consumer-directed wearable biosensing devices have shown that the measurement of egocentric views, cardiac activity, and body movement in the wild is not only possible, but that the general public is open to adopt such technology for everyday monitoring of physical health and activity (e.g., [ 86 , 87 , 88 ]), but also in various professional settings (e.g., [ 89 , 90 , 91 ]). Although such technology has been predominantly developed for adults, its ubiquitousness suggests that similar technologies for infants and young children could be received with a fair degree of openness for researching development in the ‘wild’.…”
Section: Introductionmentioning
confidence: 99%